Dairy Production in the Chuvash Republic: Success Factor Analysis - Natalya M. Suray; Alexander L. Tatochenko; Elena A. Krasil'nikova; Naila A. Teplaia; Alexey P. Mikhalev; Galina V. Zhdanova (Техника и технология пищевых производств)
The article discusses the dairy industry in the Chuvash Republic, Russia. The Russian Federation is experiencing a shortage of milk. Currently, the per capita milk consumption in the country is by more than a quarter behind the rational intake recommended by the Ministry of Health, which is 325 kg. However, the Chuvash Republic boasts 373 kg of per capita milk production, which is by 71% higher than the average data for the rest of the country, and the high quality of Chuvash milk is unanimously confirmed by leading domestic experts. The authors analyzed the success factors of milk production in the Chuvash Republic to be extrapolated on the entire domestic industry. The research relied on such demographic data as the ratio of urban vs. rural population; dairy herd data, e.g., livestock population, farm types, dairy productivity, etc.; dairy production and processing business data. The methods included systematization, generalization, grouping, statistical data processing, and analysis of temporal dynamics indicators. The Chuvash Republic has a large percentage of rural population and a lot of subsidiary dairy farms: 22 000 farms own more than 60% of dairy cows in the region and provide 55% of milk processing volumes. Subsidies allocated by the local government allow farm owners to ensure the high dairy productivity of cows. Most of the milk in the Chuvash Republic can be classified as near-organic. Leading regional milk producers have their own agricultural lands to provide environmentally friendly feed, as well as specialized premises for herd keeping and milking, retail outlets to sell their products, etc. A third of enterprises maintain the milk productivity at 7800–9200 kg, which is as high as in Denmark, the Netherlands, Great Britain, and Germany. Most Chuvash dairy farmers owe their high results to the state support funds allocated for the purchase of breeding cattle. The twelve largest milk producers in the region provide 100% of the output of drinking milk, so private farms mainly focus on meeting the needs of dairy processing enterprises. The latter also receive seasonal subsidies. The Chuvash milk miracle can be explained by the following factors: big rural population; private subsidiary farms; high-quality breeding dairy livestock; high-quality feed; good milk production and processing equipment. However, the comprehensive system of state support measures remains the most important success factor.